Vicuna oviduct mucosa: Ultrastructure and lectin affinity - Apichela, Silvana Andrea (2006)
The isthmus and uterotubal junction (UTJ) from oviducts of adult female vicunas (Vicugna vicuna) were used to study the epithelial cell ultrastructure. Scanning microphotographs revealed a mosaic pattern made up of ciliated and secretory cells with abundant microvilli. In the isthmus only a few secretory cells were present, scattered among numerous ciliated cells while in the UTJ the secretory cells prevail. The abundance of secretory cells suggests that the UTJ cells may possess special characteristics for sperm binding. No studies exist in either the vicuna or any of the other South American Camelids (SAC) concerning carbohydrates involved in sperm or embryo interactions on the oviductal surface. Identification of these sugars seems relevant to the mechanism involved in the sperm-oviduct interaction. As a first step in the determination of the molecular mechanism implicated in the formation of sperm reservoirs in the oviduct, lectin affinity for the oviductal mucosa was studied. High concentrations of glycosaminoglycans inside the two types of epithelial cells, and on their glycocalyx were observed with histochemical methods. The carbohydrates on the epithelial surface were labeled with fluorescent by lectins and analyzed with confocal scanning microscopy. The cell surface showed abundant α-mannopyranosyl, α-glucopyranosyl, β-galactosyl, N-acetyl glucosamine, and N-acetylneuraminic acid residues and few α-linked N-acetyl galactosamine residues. Neither α-l-fucopyranosyl nor β-N-acetyl galactosamine residues were observed in any part of the oviduct. The distinct ultrastructural characteristic of the UTJ as well as the presence of high concentrations of sugar residues on the mucosa surface of this portion of the oviduct could be related to its function as a sperm reservoir.